Afectaciones emocionales percibidas por los pacientes con deficiencia renal crónica y sus familiares, en el centro médico DAVITA S.A.S. en el distrito especial, turístico y cultural de Riohacha. (2020)
Abstract Objective: To understand the emotional affectations perceived by patients with chronic kidney failure and their families, at the DAVITA S.A.S medical center in the special, tourist and cultural district of Riohacha. Materials and methods: This research is qualitative of a phenomenological nature, with a typical and voluntary case sampling, 4 participants were approached, who met the criteria of our study, with prior informed consent, where 4 in-depth interviews were conducted, they were recorded and transcribed verbatim by telephone as the interviewees responded. They were developed in the city of Riohacha with patients and their relatives, who are users of the DAVITA SAS medical center. Results: From the study carried out, 25 codes were obtained, which allowed us to give a description of the investigated phenomenon, such as: dependence on treatment, change in lifestyle, emotional involvement, feelings of burden for the family, lack of psychological support, dependence on treatment, change in lifestyle, among others. Conclusions: chronic kidney failure is a chaotic disease that affects not only the patient physically but also in his emotional state and in his social environment. Therefore, it has a great influence on quality of life. In the same way, these conditions also affect the family nucleus, especially the direct caregiver of the patient. Only with the simple fact of them depending on someone to help them carry out daily activities that they carried out on their own before the illness, generates a negative impact on them due to the drastic changes they must stop in their diet, treatment, and work activities. Changing your perspective of seeing the world and accepting your own illness. Know the benefits that dialysis therapy brings to their lives, taking into account the recommendations and care necessary for the treatment to work properly. In addition, it highlights the importance of emotional support from a professional psychologist, as well as the family and the interdisciplinary team that provide services to those with kidney problems. Generating the patient a source of motivation, of tranquility forgetting those situations that cause him all stress, anger, sadness, fear among others because of his pathology. Key words: Chronic kidney failure, peritoneal dialysis, phenomenology, emotional support, negative emotions